2005
DOI: 10.1021/jp045206r
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron Radiation Effects on Catalytic Systems As Probed with a Combined In-Situ UV−Vis/XAFS Spectroscopic Setup

Abstract: UV-vis spectroscopy was used in a combined in-situ UV-vis/XAFS spectroscopic setup to study the synchrotron radiation effect on aqueous homogeneous copper solutions. Two different systems were studied. In the first study, the focus was on a copper bipyridine-catalyzed oxidation of benzyl alcohol to benzaldehyde with 2,2,6,6-tetramethylpiperidinyl-1-oxy and base as cocatalysts. It was found that when the reaction mixture is exposed to the X-ray beam, the features present in the in-situ UV-vis spectrum develop d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 25 publications
(38 reference statements)
4
72
0
2
Order By: Relevance
“…This is illustrated in Figure 9 by the spectra of sample a, obtained at three different stages in time. As reported recently, [22] the appearance of this pre-edge feature can be assigned to the reduction of Cu 2 + to Cu 1 + . Under influence of the X-ray beam, radiolysis of the water (present in the micropores of the zeolite material) occurs.…”
Section: Exafs Analysissupporting
confidence: 75%
“…This is illustrated in Figure 9 by the spectra of sample a, obtained at three different stages in time. As reported recently, [22] the appearance of this pre-edge feature can be assigned to the reduction of Cu 2 + to Cu 1 + . Under influence of the X-ray beam, radiolysis of the water (present in the micropores of the zeolite material) occurs.…”
Section: Exafs Analysissupporting
confidence: 75%
“…Reduction of Cu 2+ in the presence of chloride and bromide anions, but not in the case of nitrate and sulfate, can be explained by the ability of the nitrate and sulfate to scavenge the hydrated electron, whereas the chloride and bromide are known to be possible OH • radical scavengers. 13,25,35 Indeed with the exception of the imidazole ligand, in every case when the [SO 4 2-] is high (100 mM), copper reduction is suppressed. This leads us to conclude that the hydrated electron is most likely to be responsible for reduction of the copper in this solution, but it is not clear whether this occurs via direct interaction with the Cu 2+ or via the ligand.…”
Section: Resultsmentioning
confidence: 99%
“…It is most likely that this is caused by heating of the solution by the X-ray beam, which, over the period of time that these measurements were taken, can become significant. 4,13 However, the reduction process is much quicker than the rate of heat transfer, suggesting that physical heating is not a major contributor to the reduction process. From Figures 3b and 7b it can clearly be seen that the reduction process occurs rapidly on the right-hand site, where the X-ray beam enters the cuvette.…”
Section: Resultsmentioning
confidence: 99%
“…Weckhuysen and coworkers [90,91] have designed a combined in-situ UVvis/XANES setup to probe the influence of X-rays on aqueous homogeneous copper solutions. They found that that X-rays had effect on the nucleation behavior of nanoparticles due to the radiolysis of water.…”
Section: Reviewsmentioning
confidence: 99%